West Seti Hydro-electric Project - Thanju, Jeewan Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 60